E-Module Based on Role-Playing Learning Model with Scientific Approach to Improve Conceptual Mastery and Problem-Solving Skill on Fluid Dynamics - Christina Martha; Edi Supriana; Sunaryono Sunaryono (Universitas Lambung Mangkurat, 2023)
Fluid dynamics is the basic knowledge of technology development that is important to be mastered, but students still have difficulties with it. This research aims to determine the students’ increased conceptual mastery and problem-solving skills using e-module. The method of this study uses the quasi-experimental pre-test-post-test control group research design. Each student is given questions on pre-test and post-test conceptual mastery in multiple-choice and problem-solving skills in the form of descriptions. Student answers were analyzed with descriptive statistics, the Wilcoxon, and the n-gain tests. After the e-module was implemented, the increase in conceptual mastery of the experimental class was higher than the control class, with an n-gain value of 0.69 (moderate) for the experimental class and 0.46 (moderate) for the control class. The increase in the problem-solving skill of the experimental class was higher than that of the control class, with an n-gain value of 0.59 (intermediate) for the experimental class and 0.28 for the control class (novice). So, this e-module can improve students' conceptual mastery and problem-solving skills. The reason is caused by the learning process of experimental students who can learn actively, independently, intensively, and repeatedly using the e-module for conceptual mastering by the stages of the scientific approach through role-playing.